Three Application Scenarios for Use in the myCourse Educational Environment - Giouvanakis, Thanasis; Fragidis, Garyfallos; Koumpis, Adamantios (International Journal of Emerging Technologies in Learning (iJET), 2011)
In order for a user to develop rich and valid knowledge structures, not only is considerable predefined content required, but other equally important types of knowledge as well. In other words, to display real understanding and to build and extend their knowledge structures, users have to call on several resources as well as representation, retrieval and construction mechanisms. Apart from the specific content, on which traditional educational environments focus on, a user depends heavily on general content knowledge and on systems of knowledge that is more abstract and elusive than typical content. In this article, we document our myCourse approach presenting three application scenarios. In these scenarios, knowledge creation is a process of emergence and co-evolution of the individual, the social group and the wider society.